2022
DOI: 10.3389/fcvm.2022.913588
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Complex Percutaneous Coronary Interventions

Abstract: BackgroundAccumulated experience combined with technological advancements in percutaneous coronary interventions (PCI) over the past four decades, has led to a gradual increase in PCI utilization and complexity. We aimed to investigate the temporal trends in PCI complexity and the outcomes of complex PCI (C-PCI) in our institution.MethodsWe analyzed 20,301 consecutive PCI procedures performed over a 12-year period. C-PCI was defined as a procedure involving at least one of the following: Chronic total occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Performance and technologies (e.g., thickness, material, released drugs, etc.) of coronary intervention have improved; however, the proportion of high-risk procedures such as LM PCI or bifurcation PCI has increased over time [ 34 ]. In addition, a domain such as age is a high risk factor for ischemia and, simultaneously, a high risk factor for bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Performance and technologies (e.g., thickness, material, released drugs, etc.) of coronary intervention have improved; however, the proportion of high-risk procedures such as LM PCI or bifurcation PCI has increased over time [ 34 ]. In addition, a domain such as age is a high risk factor for ischemia and, simultaneously, a high risk factor for bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the case of the DAPT and DES-LATE trials, which are representative studies that showed the effectiveness of the extended DAPT strategy, past 1st generation stents accounted for approximately 40 and 70% ( 2 , 32 ). A recently published paper has shown that the results may differ if a reanalysis is performed by applying this trend ( 33 ). In real-world clinical practice, the risk of high ischemia and high bleeding is high, and the risks increase as the aging society progresses ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complex coronary artery disease (CCAD), a lesion type with great difficulty and a low success rate in revascularization, is accompanied by a higher rate of major adverse cardiac and cerebrovascular events (MACCE) ( 1 , 2 ). The 10-year mortality rate of three-vessel disease, chronic total occlusion, and left main lesion after percutaneous coronary intervention (PCI) is up to 21, 27.6, and 28%, respectively, much higher than the 18.6% for general lesions ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%